Certifying Software Component Performance Specifications - Groenda, Henning (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2013)
In component-based software engineering, performance prediction approaches support the design of business information systems on the architectural level. They are based on behavior specifications of components. This work presents a round-trip approach for using, assessing, and certifying the accuracy of parameterized, probabilistic, deterministic, and concurrent performance specifications. Its applicability and effectiveness are demonstrated using the CoCoME benchmark.